Integral inequalities for mappings whose derivatives are (h, m, s)−convex modified of second type via Katugampola integrals - Bayraktar, Bahtiyar (2022)
Fil: Bayraktar, Bahtiyar. Universidad de Bursa Uludağ. Facultad de Educación; Turkia.